Pengaruh Risiko Pasar dan Risiko Kredit terhadap Profitabilitas Perusahaan - Mawarti, Nufikha Ayu; Keristin, Usnia Wati (PUBLIKASI RISETMAHASISWA AKUNTANSI, 2023)
In this study, the aim is to formulate whether a company's profitability is influenced by market risk and credit risk. The objective is to analyze the profitability of companies influenced by market and credit risks. This research study utilizes secondary data from the financial reports of banks from 2018 to 2022. The population for this study consists of 47 banking companies. The data collection technique employed in this study is documentation. A total of 33 companies are selected as samples using purposive sampling. The research conducts hypothesis testing through multiple linear regression analysis. The results indicate that market risk has a positive and significant partial effect, while credit risk has a significant negative impact on profitability. Market risk and credit risk jointly have a significant influence on profitability.